Effect of Second hand Smoke on Arterial Stiffness among Healthy Women - Sariban, Suriyati; Mohd Yusoff, Siti Suhaila; Shaaban, Juwita; Mohd Noor, Norhayati; Mohamed Yusoff, Harmy (Bangladesh Journal of Medical Science, 2019)
Introduction: Arterial stiffness is recognised as a significant cardiovascular risk factor and an independent predictor of all causes of cardiovascular death. Women are the largest population exposed to cigarette smoke either at work or from their partner. The objectives of this study are to compare the arterial stiffness (augmentation index and pulse wave velocity) between second hand smoke (SHS) and non second hand smoke (non-SHS). Designs and method: Comparative cross-sectional study was conducted among 118 healthy female subjects (64 SHS and 54 non- SHS). The women were in the SHS group if their spouse is a smoker and they had an exposure to cigarette smoke for at least three years, minimum of15 minutes two days a week. Pulse wave analysis and pulse wave velocity was used to study the arterial stiffness. Pulse wave analysis reported as percentage of augmentation index. Pulse wave velocity equal to carotid femoral distance (meter) divided by time (second) Results: The mean augmentation index (AIx) for SHS groups was 17.9 (SD7.06) and for non SHS groups was 20.7(SD6.11). The mean of Pulse wave velocity was 8.94 (SD1.36) in SHS groups and 9.02 (SD8.68) in non SHS groups. ANOVA and ANCOVA shown significance difference in crude mean (p = 0.047) and estimated marginal mean (p = 0.028) of augmentation index between SHS and non - SHS after controlling for age and BMI. However, there was no significant difference in crude mean (p = 0.795) and estimated marginal mean (p = 0.716) pulse wave velocity between SHS and non - SHS after controlling for age and BMI. Conclusion: An increase in augmentation index amongst non SHS in this study most probably due to exposure to environmental tobacco at work compared to exposure to spouse’s smoke Bangladesh Journal of Medical Science Vol.18(2) 2019 p.340-346